Asian Handbook for Theological Education and Ecumenism - Antone, Hope; Longchar, Wati; Bae, Hyunju; Po Ho, Huang; Werner, D. (Dietrich); Hutarabat-Lebang, Ery; Tveit, Olav Fykse; Ju, Kim Young (Fortress Press, 2013)
This impressive and comprehensive publication focuses on key resources for teaching about Christian unity and common witness in Asian contexts. This collection of articles reflects the ongoing need to wrestle both with the texts of biblical tradition and with contemporary contexts. Asian Christians reflect theologically on what it means to be the church in Asia at particular times, expressing unity in Christ and witnessing to the love of Jesus amid the challenges posed by changing and pluralistic realities. This handbook will contribute significantly in the area of theological education.